UTAR Lost and Found Management System - Chin, Yun Ting (2020)
People lose things occasionally. Scattered and unorganized lost and found information can have a significant impact on the possibility to get back the lost items. The information cannot reach the rightful owner if they are not well-managed. Hence, the UTAR lost and found management system project was implemented to provide a standardized, centralized way to handle lost and found items in UTAR. The project objectives are to analyze the existing lost and found problems in UTAR as well as the features of similar systems and develop a cross-platform lost and found management system to improve the efficiency and effectiveness in managing and organizing the lost and found items in UTAR. The result showed the user preference between web application and mobile application are almost equal based on the survey conducted. Thus, a cross-platform application was developed so users can access through a web browser or mobile application. The basic functionality of the application includes viewing, reporting and updating lost and found items, submitting claims, selling and bidding expired items. MySQL database was used as the system database. The framework of the web application is Laravel while the mobile application is React Native. The adopted methodology in this project is prototyping methodology. Unit testing, integration testing and user acceptance testing were conducted to evaluate the system. Based on the user acceptance testing conducted, most of the respondents are satisfied with the function of the system. Some respondents suggested to improve the user interface of mobile application so it can be more attractive for users.